MENGEJAR PEMULIHAN: SEBUAH UPAYA MENCAPAI PENYEMBUHAN DALAM KELUARGA BATAK KRISTEN - Hans Hennery Purba (Bethel Press, 2023)
Various kinds of issues are present in human life. Some lead to complex conflicts and relationships that negatively affect many parties. In this paper, the author observes culture in the context of the Batak tribe, one of the root causes of family conflict. This article examines the influence of culture, which has played a significant role in generating conflict between parties and becoming an obstacle to restoring relations. The method used is a case study of the process of pastoral counseling. The study results show that conflicts within the Batak ethnic family can be mediated with a comprehensive understanding of the Batak ethnic group. With a typical understanding, conflicts can be resolved properly.